2021
DOI: 10.1002/mcf2.10178
|View full text |Cite
|
Sign up to set email alerts
|

Relative Catch Performance of Two Gear Modifications Used to Reduce Bycatch of Undersized Fish and Shrimp in Mediterranean Bottom Trawl Fisheries

Abstract: The catch of large quantities of sublegal-sized fish and shrimp is a pervasive feature of bottom trawl fisheries, particularly in the Mediterranean demersal mixed fisheries where regulations traditionally allow small mesh sizes. To address these concerns, two bottom trawl net selectivity trials were carried out in 2019 and 2020 on fishing grounds worked by the trawl fleet of Spanish Mediterranean, under normal commercial operating conditions with volunteer trawlers of the local fleet. The traditional otter bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…The authors observed a significant reduction, in the experimental net, of the catch of undersized individuals, but also of legal sized individuals. The same results were obtained by Maynou et al (2021). They tested two experimental nets that, besides reducing the extension piece mesh size (50 mm T90 vs. 53 mm diamond of standard net), 13.2 1.9 (Tokaçet al, 1998) maintained or increased the number of meshes around extension circumference (210 and 220 vs. 210 of standard net) and, in the 40 mm square mesh codend, reduced the number of meshes around circumference (106 and 104 vs. 130 of standard net).…”
Section: Standardsupporting
confidence: 87%
“…The authors observed a significant reduction, in the experimental net, of the catch of undersized individuals, but also of legal sized individuals. The same results were obtained by Maynou et al (2021). They tested two experimental nets that, besides reducing the extension piece mesh size (50 mm T90 vs. 53 mm diamond of standard net), 13.2 1.9 (Tokaçet al, 1998) maintained or increased the number of meshes around extension circumference (210 and 220 vs. 210 of standard net) and, in the 40 mm square mesh codend, reduced the number of meshes around circumference (106 and 104 vs. 130 of standard net).…”
Section: Standardsupporting
confidence: 87%
“…The results obtained by those experiments are contrasting. In the case of Sola and Maynou (2018a) and Maynou et al (2021), the T90 placed in the extension piece determined an increase in the size at first catch of European hake, well above the MCRS, as well as an increase in the catch rates of this species. For red mullet and striped red mullet, the legal mesh size of codend (40 mm square or 50 mm diamond) already allows catching individuals larger than the MCRS and the use of the T90 in the extension piece would mainly result in a commercial catch reduction.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, some experiments have been carried out in the Mediterranean to evaluate whether the T90 configuration can lead to a significant increase in selectivity if applied to different sections of the trawl net, other than the codend. Sola and Maynou (2018a) and Maynou et al (2021) in the Catalan Sea, and Petetta et al (2022) in the Adriatic Sea experimented trawl nets with the T90 configuration placed in the extension piece, i.e. the section of the net just in front of the codend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mediterranean Sea hosts a large trawl fishery that is characterised by small mesh sizes (40‐mm square mesh) to capture deep‐water shrimp species alongside demersal fish species (Sala et al, 2015). However, this also results in high levels of bycatch that can account for up to 65% of total catch including the exploitation of juvenile and undersized individuals (Maynou et al, 2021; Tsagarakis et al, 2014). Indiscriminate trawling practices have also resulted in substantial alterations in benthic community composition in this region with many VME indicator species now largely absent from these areas (De la Torriente Diez et al, 2022; Grinyó et al, 2020; Pierdomenico et al, 2018).…”
Section: Discussionmentioning
confidence: 99%